Car cooling system during parking using blowe - Amiruddin, Ahmad (2007)
The main objective for project 'Car cooling system during parking using blower' is to give the student experience in modify the actual system to a better system. Final year diploma student is tasked to finish this project as blower system model that will be use as apparatus in Laboratory of Mechanical Engineering in Universiti Malaysia Pahang. As per present wiring, the blower is rotating in one direction, this project will change the rotation to reverse rotation. The main part used in this wiring system is relay 87a and thermal sensor. In finishing this process need to be documented because it will be the main reference that useful for student that involved in producing new system of wiring for present car blower in market. Several experiments are done to see whether it work or not. An experiment was carried out under sun light for couples of days use real car to get the decrease effect of heat car compartment when this system use. Several weaknesses detected after the experiment completed, for instance the use of battery power that caused car facing problem to ignite. There are several method to solve this problem, one using solar power or adding another 12V battery to the car. If this problem solved, the system could have potential to be introduced in automotive industry.